Applications of Educational Technology in Solving Learning Problems - Furtasan Ali Yusuf; Linda Wijayanti; L Lukas; Sandra Octaviani; Enny Widawati (CV. Media Digital Publikasi Indonesia, 2023)
Educational technology in its contribution to the management and learning of education is opening up knowledge horizons about changing strategic environments. We need the growth of science and technology caused by learning and learning activities of innovation. Speaking in this case is inadequate because the concept of technological studies provides a formula for how to bring teaching and learning activities. Then, the application of educational technology, especially ICT (Information and Communication Technology) in education to overcome learning problems has a number of requirements. For example, the need for large investment costs and energy that are skilled in managing and developing education and utilizing technological advancements that will support the process of learning. It is noteworthy that education is a long-term investment. Therefore, investment in basic education facilities must be calculated with future educational outcomes